The management of chieftaincy records in Ghana: an overview - Adams, M. (African Journal of Library, Archives and Information Science, 2005)
In many developing countries, like Ghana, the chieftaincy institution serves both administrative and advisory roles to the government in community affairs. Using data obtained through a survey, this study examined the management of chieftaincy records in Ghana. The study revealed that chieftaincy records serve as source material for both traditional administration and research. However, requests for records as research material tilt towards land administration and the history of the chieftaincy stools and land. The study concludes with recommendations on how to ensure effective management of chieftaincy records for both current and future use.
Keywords: Ghana; chieftaincy archives; chieftaincy institution; government in community affairs